━━━━━━━☆☆━━━━━━━
▹ Answer
<em>q = 16</em>
▹ Step-by-Step Explanation
3(q - 7) = 27
3q - 21 = 27
Add 21 to both sides:
21 + 21 = na
27 + 21 = 48
3q = 48
Divide both sides by 3:
3/3 = q
48/3 = 16
q = 16
Hope this helps!
CloutAnswers ❁
━━━━━━━☆☆━━━━━━━
Given the points A and B
The coordinates of point A = ( 3 , 1 )
The coordinates of point B = (-1 , -1)
The midpoint of AB, is the point C
C will be calculated as following :
![C=\frac{A+B}{2}=\frac{(3,1)+(-1,-1)}{2}=\frac{(3-1,1-1)}{2}=\frac{(2,0)}{2}=(1,0)](https://tex.z-dn.net/?f=C%3D%5Cfrac%7BA%2BB%7D%7B2%7D%3D%5Cfrac%7B%283%2C1%29%2B%28-1%2C-1%29%7D%7B2%7D%3D%5Cfrac%7B%283-1%2C1-1%29%7D%7B2%7D%3D%5Cfrac%7B%282%2C0%29%7D%7B2%7D%3D%281%2C0%29)
so, the midpoint of AB = (1 , 0 )
15% = 0.15
234.00 x 0.15 = 35.10
234.00 - 35.10 = 198.90
The camera will cost $198.90 after the discount.
-x - y = 8
2x - y = -1
Ok, we are going to solve this in 2 parts. First we have to solve for one of the variables in one of the equation in terms of the other variable. I like to take the easiest equation first and try to avoid fractions, so let's use the first equation and solve for x.
-x - y = 8 add y to each side
-x = 8 + y divide by -1
x = -8 - y
So now we have a value for x in terms of y that we can use to substitute into the other equation. In the other equation we are going to put -8 - y in place of the x.
2x - y = -1
2(-8 - y) - y = -1 multiply the 2 through the parentheses
-16 - 2y - y = -1 combine like terms
-16 - 3y = -1 add 16 to both sides
-3y = 15 divide each side by -3
y = -5
Now we have a value for y. We need to plug it into either of the original equations then solve for x. I usually choose the most simple equation.
-x - y = 8
-x - (-5) = 8 multiply -1 through the parentheses
-x + 5 = 8 subtract 5 from each side
-x = 3 divide each side by -1
x = -3
So our solution set is
(-3, -5)
That is the point on the grid where the 2 equations are equal, so that is the place where they intersect.